Renewable energy technologies & the water infrastructure : a technical book-report by the Advancing Renewable Energy Technologies Committee (2018-2020) - Chitikela, S. Rao; Gullapalli, Venkata; Ritter, William F. (American Society of Civil Engineers, 2021)
"Renewable Energy Technologies and the Water Infrastructure provides an in-depth look at policy, regulation, and the development and application of renewable energies into existing water infrastructure"--